Clinical study of Tongdu Shujin decoction in the treatment of ankylosing spondylitis with cold-dampness obstruction type: Study protocol for a randomized controlled trial. Issue 6 (10th February 2023) - Wang, Zihua; Du, Mingrui; Li, Jigao; Shi, Dongliang; Wang, Hejun; Li, Huan; Guo, Hongtao
Abstract : Background: Ankylosing spondylitis (AS) has a high incidence, and severe cases can lead to spinal deformity and even joint fusion, which causes a huge burden on patients life, work and psychology. Tongdu Shujin decoction (TDSJ) has a definite effect in the treatment of ankylosing spondylitis, so we designed a randomized controlled trial to observe the efficacy of TDSJ in the treatment of AS, and to evaluate its safety. Methods: In this randomized controlled trial, 80 eligible patients were randomly assigned in a 1:1 ratio to a treatment group TDSJ and a control group (celecoxib capsules in combination with thalidomide tablets) for 8 weeks. Visual analogue scale, bath ankylosing spondylitis disease activity index, bath ankylosing spondylitis functional index, and traditional Chinese medicine syndrome scores will be used as primary indicators. Erythrocyte sedimentation rate, C-reactive protein, spinal mobility (figure-ground distance, occipital tubercle-wall distance, Schober test) will be used as secondary indicators. Vital signs (respiration, heart rate, body temperature, blood pressure, electrocardiogram), blood routine, urine routine, stool routine, liver function, and renal function will be used as safety indicators. The primary and secondary indicators will be detected at 0th and 8th week, while safety indicators at 0th, 4th, and 8th week. Discussion: This study will provide high-quality clinical evidence for the efficacy and safety of TDSJ in the treatment of AS.